The Art of Isan Molam Folk Performance as a Medium for Meaning-Making, Audience Engagement, and Audience Loyalty - Kainunapa, Phacharanat (Thammasat Journal, 2026)
Mor Lam is a traditional folk performance art that originated in Northeastern Thailand (Isan). It serves both as a form of entertainment and as a medium for storytelling, using Isan Luk Thung (folk country music) as its primary mode of expression. The content of Mor Lam performances reflects the culture, traditions, and way of life of the Isan people. Therefore, Mor Lam is not merely a performance for entertainment but also functions as a medium for meaning making and audience engagement. This academic article aims to: 1) Explore the roles and development of Mor Lam 2) Examine Mor Lam as a medium, through an analysis of audience interpretation and responses to its content and presentation and 3) Identify the factors that influence audience perception and participation, such as social and cultural contexts, personal experiences of the audience, and other related media. The study employs theoretical frameworks and concepts from communication and media studies to gain a deeper understanding of the evolution of Mor Lam as a complex and multidimensional form of indigenous media. This research highlights how Mor Lam, deeply rooted in Isan agricultural life, has evolved from its traditional origins into the digital era, influenced by technology and communication.